The Influence of Differentiated Instruction on Senior High School’s English Learning Outcomes - M. Jufrianto; Muhammad Basri; Iskandar Iskandar; Reskyani Reskyani; Isna Humaera; Mustaqimah Mustaqimah; Rahyuni Rahyuni (JELITA, 2024)
The goal of this research is to use differentiated instruction in English in order to improve student learning outcomes. This class X research was carried out at UPT SMA Negeri 3 Takalar. This study employs structured interviewing methods, recording, and observation in a qualitative descriptive research design. According to the research, 20 students, or 13 students in total, had a completeness score in cycle I mathematics learning of 65%, and 7 students, or 35% of the students, did not achieve the passing requirement. Then, in cycle II, the comprehensiveness of the instruction yields an 81.50% acquisition in English for a total of 17 pupils, as well as children who have met the score.